2012
DOI: 10.1017/s1368980012004077
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient intake and status in Central and Eastern Europe compared with other European countries, results from the EURRECA network

Abstract: Objective: To compare micronutrient intakes and status in Central and Eastern Europe (CEE) with those in other European countries and with reference values. Design: Review of the micronutrient intake/status data from open access and grey literature sources from CEE. Setting: Micronutrients studied were folate, iodine, Fe, vitamin B 12 and Zn (for intake and status) and Ca, Cu, Se, vitamin C and vitamin D (for intake). Intake data were based on validated dietary assessment methods; mean intakes were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 62 publications
5
34
0
3
Order By: Relevance
“…The levels of serum/plasma folate reported in a recent publication on micronutrient intake and status is Europe were 14–23 nmol/L [46], and in the publication by Duffy et al [3], the levels were in the range 6–24 nmol/L and this is in line with the range observed in this review (5–31 nmol/L).…”
Section: Discussionsupporting
confidence: 88%
“…The levels of serum/plasma folate reported in a recent publication on micronutrient intake and status is Europe were 14–23 nmol/L [46], and in the publication by Duffy et al [3], the levels were in the range 6–24 nmol/L and this is in line with the range observed in this review (5–31 nmol/L).…”
Section: Discussionsupporting
confidence: 88%
“…The average daily intake of iodine in the general population is less than that indicated by WHO, at the European level, where iodine deficiency affects mainly the child population [43], and all over the Italian territory (85–88 µg/day vs. 150 µg/day) [44]. …”
Section: Micronutrientsmentioning
confidence: 99%
“…Previous systematic reviews of fruit, vegetable and micronutrient intakes in CEE, FSU and WE countries used data from studies which had been conducted separately in the two regions [12, 13]. These reviews found that the methodological differences between studies seriously limited the interpretation of the results, and emphasised that the lack of comparable data was especially important in CEE and FSU countries.…”
Section: Introductionmentioning
confidence: 99%